Manajemen Fundraising Potret Yayasan Badan Wakaf Universitas Islam Indonesia Yogyakarta dalam Menggalang Wakaf - Miftahul Huda (Justicia Islamica, 2014)
The development of a waqf nadhir is currently important in an effort to strengthen and develop waqf continuously for the benefit of mauqu}>f"˜alaih. One of the efforts of the nadhir is to raise funds/power in order to make a breakthrough so that the huge assets and potential of waqf management can be developed. The activity of raising power/funds by an institution is known in the current context as fundraising activity. Therefore, this paper describes and explores the uniqueness of waqf management from a fundraising perspective in the Waqf Board Foundation of Universitas Islam Indonesia Yogyakarta. The results of this paper show that the pattern of waqf fundraising is unique, such as the uniqueness of university-based waqf fundraising for community empowerment at the nadhir of UII Yogyakarta.